Conceptualizing Time through Idiomatic Expressions: A Comparative Study of Spanish and Uzbek Phraseological Systems - Abdullaeva Parvina Tolibjonovna, (INTEGRATION OF EDUCATION AND SCIENCE: GLOBAL CHALLENGES AND SOLUTIONS, 2026)
Abstract: This article investigates the conceptualization of time as reflected in Spanish and Uzbek phraseology, focusing on the interaction between metaphor, cognition, and cultural models. Building upon the theoretical premises of conceptual metaphor theory and linguistic relativity, the study analyzes idiomatic expressions and proverbs that encode temporal meanings in both languages. The objective is to identify shared cognitive patterns in temporal metaphorization and to determine culturally specific configurations shaped by historical, religious, and socio-economic contexts. The analysis demonstrates that while both Spanish and Uzbek rely on spatial, motion-based, and resource metaphors to structure temporal experience, their phraseological systems differ in emphasis, semantic extension, and cultural resonance. Spanish idioms frequently conceptualize time as a linear resource subject to control and expenditure, whereas Uzbek expressions often integrate cyclicality, endurance, and communal temporality. The findings contribute to cross-linguistic phraseology and intercultural semantics by highlighting the linguistic encoding of culturally embedded temporal worldviews.